1993
DOI: 10.1136/gut.34.10.1458
|View full text |Cite
|
Sign up to set email alerts
|

Improved symptom relief and duodenal ulcer healing with lansoprazole, a new proton pump inhibitor, compared with ranitidine.

Abstract: The purpose of this study was to compare duodenal ulcer healing, symptom relief, and safety of lansoprazole (a new proton pump inhibitor) given at doses of 30 mg and 60 mg, in the morning with ranitidine 300 mg at bedtime. (p=0026) also recorded greater relief of night time pain in the diary cards during the first seven days of treatment than those on ranitidine. Patients on lansoprazole 60 mg reported significantly better pain relief at their two week visit compared with those receiving ranitidine (p=0 007).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…17-1g Lansoprazole, a benzimidazole derivative, is a proton pump inhibitor that acts on the membrane Hf/ K+-adenosine triphosphatase in gastric parietal cells?0,21 This drug is being increasingly used in the treatment of duodenal ulcer, Zollinger-Ellison syndrome, and other related hyperacidic conditions. [22][23][24] In humans, lansoprazole is extensively biotransformed, mainly by hepatic oxidative metabolism.22724 Human clinical pharmacology studies have shown pronounced interindividual variability in plasma concentrations of patients receiving the same dose of lansoprazole. 24,25 Previous in vitro human liver microsome studies18,19 on the metabolism of omeprazole, a proton pump inhibitor structurally similar to lansoprazole,26 have shown that the production of the hydroxylated metabolite is mediated through CYP2C19.…”
Section: Dong-ryulmentioning
confidence: 99%
“…17-1g Lansoprazole, a benzimidazole derivative, is a proton pump inhibitor that acts on the membrane Hf/ K+-adenosine triphosphatase in gastric parietal cells?0,21 This drug is being increasingly used in the treatment of duodenal ulcer, Zollinger-Ellison syndrome, and other related hyperacidic conditions. [22][23][24] In humans, lansoprazole is extensively biotransformed, mainly by hepatic oxidative metabolism.22724 Human clinical pharmacology studies have shown pronounced interindividual variability in plasma concentrations of patients receiving the same dose of lansoprazole. 24,25 Previous in vitro human liver microsome studies18,19 on the metabolism of omeprazole, a proton pump inhibitor structurally similar to lansoprazole,26 have shown that the production of the hydroxylated metabolite is mediated through CYP2C19.…”
Section: Dong-ryulmentioning
confidence: 99%
“…8,9 However, no comparison has been made in the relief of dyspeptic symptoms in unselected patients presenting in general practice with undiagnosed acid-related dyspepsia.…”
Section: Introductionmentioning
confidence: 99%
“…In the treatment of peptic ulcer disease and gastrooesophageal re¯ux disease (GERD), the proton pump inhibitor lansoprazole has been shown to be superior to ranitidine and the other H 2 -receptor antagonists in the relief of symptoms. 8,9 However, no comparison has been made in the relief of dyspeptic symptoms in unselected patients presenting in general practice with undiagnosed acid-related dyspepsia.…”
Section: Introductionmentioning
confidence: 99%
“…Lansoprazole is a new proton pump inhibitor which produces a prolonged decrease in gastric acidity. 1,2 The drug was introduced onto the Dutch market at the end of 1993 as a 30 mg capsule indicated for the treatment of re¯ux oesophagitis and the healing of gastric and duodenal ulcers. At the time of introduction, lansoprazole had been evaluated in several thousands of patients enrolled in clinical trials.…”
Section: Introductionmentioning
confidence: 99%